METHODOLOGY FOR DETERMINING AND UPDATING CADASTRE BOUNDARIES OF AGRICULTURAL LAND BASED ON UAV (DRON) PHOTOGRAMMETRY - Mirzakarimova Gulshanoy Mirzakarimova daughter (Modern American Journals, 2025)
This study proposes a scientific and practical methodology based on UAV (drone) photogrammetry for clarifying and updating the cadastral boundaries of agricultural land plots in the Fergana region. The methodology covers the processes of geodetic linking of UAV RGB images with GNSS RTK/PPK measurements and GCP/CP reference points, creating high-resolution orthophoto products through photogrammetric processing (tie points/bundle adjustment, dense point cloud, DSM/DTM, orthophoto mosaic), and interactive delineation of plot boundaries based on them. The update stage involves improving the cadastral layers in an auditable manner based on the criteria of topological control (overlap/gap/sliver), difference register (shift, area change), and accuracy assessment (RMSE, CE90/LE90). As a result, the proposed approach serves to promptly update cadastral data, reduce geometric errors, optimize resource consumption, and ensure evidence-based decision-making in land resource management.
Keywords: UAV (drone) photogrammetry, cadastre, land parcel boundary, orthophoto mosaic, GCP/CP, GNSS RTK/PPK, DSM/DTM